ANALYSIS COMPARISON OF LIGHTWEIGHT CONCRETE WALL WITH M-SYSTEM WALL (Case Study Providentia Dei Dormitory Project) - ., Suzaeni (EXTRAPOLASI: Jurnal Teknik Sipil, 2013)
In construction project activity required innovation in order to achieve the main objectives andtargets that the project quality, cost and time. On the selection of building materials to be used, will havea considerable impact on project cost and schedule planning. Lightweight Concrete ( autoclaved AeratedConcrete ) is a product of high-tech brick that can help to entered a new era in construction. AdvantageLightweight Concrete is high-quality raw materials and environmentally friendly. Simplicity, fastnessand tidiness of the implementation is advantages of Lightweight Concrete. M-Systems is a technology inbuilding materials using a modified polystyrene as a load resistant element. Polystyrene modification isdone by providing high quality wire mesh frame and polystyrene coated with a relatively thin layer ofcoating. The advantages of the M-System s technology is not only strength load resistant, but alsoenvironmentally friendly, lighter, fire resistant, sound-proofed and strength resistant.This research aims to compare the used of Lightweight Concrete wall with M - System wall by analyzingthe difference of price.The results has got from this research is M-System wall 2.63 times more expensive than the LightweightConcrete.Keywords: Lightweight Concrete, M-System, Polystyrene, price analysis.